2019
DOI: 10.35547/im.2019.21.3.002
|View full text |Cite
|
Sign up to set email alerts
|

Генетический Полиморфизм Редких И Малораспространенных Аборигенных Донских Генотипов L

Abstract: История виноградарства на Дону насчитывает несколько веков, местные сорта винограда многообразны и специфичны. Микросателлитные маркеры широко используются для генотипирования сортов и подвоев винограда, при изучении происхождения сортов и анализе их родословной. Целью исследования было изучение выборки редких и малораспространенных автохтонных донских сортов и сравнение их с другими аборигенными донскими генотипами на основе данных ДНК-анализа. В исследования включены 23 стародавних донских сорта. Генотипиров… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The results of this study showed the appearance of two centers of origin of cultivated germplasm, one in the Middle East and the other in the western part of the Mediterranean Sea. In this case, the second one gave rise to many existing Western European varieties [7][8][9]. The existence of various theoretically and practically substantiated centers of origin of plant forms suggests that the preservation of endemic relict plant forms in these centers is still possible., The territory of the Northern Caucasus and the Black Sea coast (northern regions of the Black Sea) is considered the most promising of all zones from the point of view of studying the biodiversity of grapevines [10].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed the appearance of two centers of origin of cultivated germplasm, one in the Middle East and the other in the western part of the Mediterranean Sea. In this case, the second one gave rise to many existing Western European varieties [7][8][9]. The existence of various theoretically and practically substantiated centers of origin of plant forms suggests that the preservation of endemic relict plant forms in these centers is still possible., The territory of the Northern Caucasus and the Black Sea coast (northern regions of the Black Sea) is considered the most promising of all zones from the point of view of studying the biodiversity of grapevines [10].…”
Section: Introductionmentioning
confidence: 99%